Pengetahuan Masyarakat Sekitar Khdtk Mungku Baru Dalam Pemanfaatan Hasil Hutan Bukan Kayu - Pigo Despriando; Sari Marlina; Ardiyansyah Purnama (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2026)
The Special Purpose Forest Area (KHDTK) Mungku Baru has great potential in developing non-timber forest products (NTFPs) that can provide economic benefits for surrounding communities. This research aims to analyze the level of knowledge of communities around KHDTK Mungku Baru in utilizing NTFPs as an alternative source of sustainable income. The research method uses a qualitative approach with in-depth interview techniques and participatory observation of communities around the area. The research results show that communities around KHDTK Mungku Baru have fairly good traditional knowledge about NTFP utilization, but are still limited in processing and marketing aspects. The most well-known NTFP commodities among the community include rattan, bamboo, forest honey, resin, and traditional medicinal plants. The main constraints faced are lack of market access, limited processing technology, and suboptimal government support in NTFP development. The recommendations given are the need to increase community capacity through training, formation of local institutions, and development of sustainable NTFP value chains.